Participatory governmentality: social network transitions in Malaysia’s mental healthcare - Teoh, Sing Fei (2022)
With the growing use of networking communication technologies and social media networks in Malaysian and Asian Pacific societies, prospects for public health governance and health communications have been shifting. Based on Manuel Castells’ conceptual framework of the ‘network society’, this dissertation conducts a structural analysis of Malaysia’s mental health governance. This research serves as a case study to respond to a broader objective to understand the evolution of national governmental practices and rationality in a transitioning Malaysian society. These (1) micro and (2) macro objectives form the primary research framework for the dissertation. Nine mental health initiatives by governmental, entrepreneurial, and civil societal leaderships in contemporary Malaysian society have been purposively sampled for a qualitative content analysis. These nine sets of data mainly come from organisational websites, official institutional documents, social networking platforms, and public media commentaries. Having studied the participatory network transitions, affordances, and practices in Malaysia’s new mental healthcare landscape, this dissertation critically discusses the emerging issues and challenges in this domain of societal governance, and proposes a new conceptual model of ‘participatory governmentality’ for emergent network societies. Here, the findings reveal that, in response to the gradual decline in the hegemony of traditional institutions, emergent affordances in Malaysia’s network society are being harnessed for (1) rebuilding a trusted, transparent system of collaborative governance, and (2) fostering participatory networks and public diplomacy for improving the quality of life (QOL) of the nation’s citizenries. Hence, it is suggested that ordinary citizens, societal and governmental leaderships, and researchers further investigate into how mobile communications can provide the means for improving or reforming self-care routines, for transparent participation of citizenries in governmental decision-making processes, and for building cross-sectoral solutions and public diplomatic practices in Malaysia.